Health care networks: the role of the family health team in child hearing loss - Silva,Jullyane Florencio Pachêco da (2017)
ABSTRACT Purpose: to understand the network performance of family health staff on child hearing loss. Methods: a qualitative case-study research. Data collection consisted in three focus groups of family health staff from district IV in the city of Recife. Data were analyzed by meaning condensation. Results: most professionals perform their functions individually, which might weaken the comprehensive health care. Additionally, the lack of interaction with other complexity levels to meet the various actions and the absence of counter-reference required by the staff prevents the child's ongoing care. Conclusion: the teams’ organization and their relationships with other health care services are surrounded by weaknesses that make assistance ineffective regarding hearing health.